Inclusion, accessibility and permanence: the right to higher education for people with hearing impairment - Sartoreto de Oliveira Martins, Sandra Eli [UNESP]; Napolitano, Carlo Jose [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2017)
The increasing number of students with hearing impairment enrolled in higher education has become a recurring fact nowadays. This paper will discuss the achievements and advances of deaf students who use the Brazilian Sign Language (Libras) in higher education. Due to the multiplicity of factors and the consolidation of the inclusive education, this text will also discuss legal and judicial aspects that enable the access and permanence of these individuals in the university. Considerations presented in the text aim to demystify misleading actions on social and individual rights of this group, that, like the affirmative actions, should strive for the prevalence of equal opportunity and justice as supreme values of a fraternal, pluralistic and inclusive society in an educational context.
Keywords: Public policies; Higher education; Inclusion; Deafness; Libras